2014
DOI: 10.1002/ijc.28702
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial bacteria stimulate host immune cells to counteract dietary and genetic predisposition to mammary cancer in mice

Abstract: Recent studies suggest health benefits including protection from cancer after eating fermented foods such as probiotic yogurt, though the mechanisms are not well understood. Here we tested mechanistic hypotheses using two different animal models: the first model studied development of mammary cancer when eating a Westernized diet, and the second studied animals with a genetic predilection to breast cancer. For the first model, outbred Swiss mice were fed a Westernized chow putting them at increased risk for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(154 citation statements)
references
References 46 publications
11
143
0
Order By: Relevance
“…Subsets of CD-1 mice who had been treated with NWD in-utero subsequently received in their drinking water an anti-inflammatory strain of Lactobacillus reuteri ATCC-PTA-6475 cultivated as described elsewhere (8,9), with live organisms supplied at a starting dosage of 3.5×10 5 organisms/mouse/day in drinking water (4). Live bacterial counts in water bottles were calculated to be 1.4×10 6 colony forming units (CFU) per mouse on day 1, 4.1×10 5 CFU on day 2, and 1.1×10 5 CFU on day 3, and L reuteri was detectable by PCR in feces and bowel of mice undergoing the dosing regimen, as described in detail in Lakritz et al (2014) (4). Control mice received regular drinking water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsets of CD-1 mice who had been treated with NWD in-utero subsequently received in their drinking water an anti-inflammatory strain of Lactobacillus reuteri ATCC-PTA-6475 cultivated as described elsewhere (8,9), with live organisms supplied at a starting dosage of 3.5×10 5 organisms/mouse/day in drinking water (4). Live bacterial counts in water bottles were calculated to be 1.4×10 6 colony forming units (CFU) per mouse on day 1, 4.1×10 5 CFU on day 2, and 1.1×10 5 CFU on day 3, and L reuteri was detectable by PCR in feces and bowel of mice undergoing the dosing regimen, as described in detail in Lakritz et al (2014) (4). Control mice received regular drinking water.…”
Section: Methodsmentioning
confidence: 99%
“…Impaired regulatory capacity leads to uncontrolled immune inflammatory responses, obesity and cancer later in life (2, 3). Our recent studies in mice have shown that Westernized diet (NWD)-associated obesity and cancer coincide with changes in gastrointestinal (GI) tract microbial communities and immune regulatory capacity preventable by dietary enrichment with beneficial bacteria(47). We test here whether these postulated effects of gut microbes transcend generations.…”
Section: Introductionmentioning
confidence: 99%
“…Oxytocin modulates interferon- γ (IFNγ) and CD25 expression culminating in robust yet tightly regulated immunity. As a consequence of eating probiotic organisms, aged mice displayed superb wound healing capacity 7 , 8 . In this setting, mice were also resistant to both western diet-induced and ErbB2 oncogene overexpression-associated mammary carcinogenesis 8 …”
Section: Gi Tract Bacteria Affect the Immunological And Metabolic Promentioning
confidence: 99%
“…This effect was caused by the elevation of the pro-inflammatory cytokines IFN-γ, TNF-α and IL-2 levels and increased NK cell activity [115] . cells by LAB and their beneficial effect against mammary carcinoma was analyzed using two mice models [116] . In one model, mice were fed a Westernized chow increasing risk for development of mammary tumors.…”
Section: Probiotics and Cancermentioning
confidence: 99%